Damage Evolution of Rocks Containing a Set of Cross-Joints Based on Acoustic Emission Characteristics - Xiao Li; Xinquan Wang; Kangyu Wang; Hongguo Diao; He Zhang (Advances in Materials Science and Engineering)
The problem of damage rupture of jointed rocks is a hot topic of research in underground tunnel engineering. In this paper, the damage evolution characteristics of rocks containing a set of cross-joints are investigated based on particle flow code (PFC). Firstly, the jointed rock models, such as rock models with different joint cross-angles and with different joint lengths, are established based on PFC. Then, the uniaxial compression mechanical properties and acoustic emission (AE) evolution characteristics of different jointed rocks are analyzed. Finally, the damage evolution characteristics of jointed rocks are discussed based on the damage variable defined by AE counts. The research results show that the uniaxial compressive strength (UCS) and elastic modulus (E) of the jointed rock are highest when the joint cross-angle β is 60°. The UCS and E of jointed rocks show a trend of decrease with the increase of joint length. The overall trend of the AE evolution of jointed rocks does not change with the change of joint cross-angle and joint length. However, the time step of the occurrence of acoustic emission (crack initiation time) has changed. The damage evolution of jointed rocks shows three stages with the increase of stress (time): damage-free stage, slow damage increase stage, and sharp damage increase stage. The fluctuation characteristics of the damage evolution of jointed rocks are different with the change of β and LB. The damage rupture of jointed rocks begins to sprout from and expand along the tip of the joints.